Dwelling in the Human/Posthuman Entanglement of Poetic Inquiry: Poetic Missives to and from Carl Leggo - Prendergast, Monica (Journal of the Canadian Association for Curriculum Studies, 2020)
This inaugural Dr. Carl Leggo Memorial Lecture on Poetic Inquiry was delivered at the 7th International Symposium on Poetic Inquiry on October 3rd, 2019. I share a poetic conversation I have crafted out of Carl’s work that allows me, and all of us, to enter into a continuing dialogue with Carl’s words, which survive and will live on without his earthly presence. I discuss the process I undertook to create these poetic missives, in my voice and Carl’s, following the dialogue. All of the work beginning with “Dear Monica” are found poems created from Carl’s writing—his prose, not his poetry. My own poetic messages to Carl are mostly original, although they include a bit of found poetry from the literature on posthumanism. And the abecedarian poem is definitely inspired by Carl’s love of this type of poem, and his playful joy, always, in exploring the possibilities of language and poetry.